Synthesis, characterization and non-isothermal decomposition kinetics of manganese hypophosphite monohydrate - Noisong, Pittayagorn; Danvirutai, Chanaiporn; Srithanratana, Tipaporn; Boonchom, Banjong (My University, 2008)
The manganese hypophosphite monohydrate (α-Mn(H2PO2)2·H2 O) was synthesized and characterized by differential thermal analysis-thermogravimetry (TG/DTG/DTA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), X-ray powder diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The thermal transformation products form the synthesized Mn(H2PO2)2·H2O according to the thermal treatment at 160 and 450 °C were found to be α-Mn(H2PO2)2·xH2 O and Mn2P2O7, respectively. The activation energies of two decomposition reaction steps of Mn(H2PO2)2·H2O were calculated through the isoconversional methods of Ozawa and KAS. The obtained activation energies can be concluded that the reactions of the dehydration and the decomposition steps for Mn(H2PO2)2·H2O were the single and multi-step mechanisms, respectively. © 2008 Elsevier Masson SAS. All rights reserved.
Keywords: α-Manganese hypophosphite monohydrate; Non-isothermal kinetics; Thermal transformation